Efektivitas Pengelolaan Kapal Latih - Arief, Muchlis Imanullah; Syafaat, Buce Akhmad; Hadijah, Hadijah; Rohyana, Mochamad Furqon; Sugiawiharja, Egi; Setyawati, Aswanti (Institut Transportasi dan Logistik Trisakti, 2022)
The function of the training ship is as a place for education, training, demonstration and simulation at sea and as a laboratory for educational and teaching activities that develop and improve knowledge, skills, understanding and experience as well as attitudes on board. The aims of the research is to find out whether the management of the training vessel, study case on board KL MH Thamrin, is effective and efficient according to its function, and also to find out whether the management of the training vessel is optimal for human resource development under the Sea Transportation Human Resources Development, as well as to find out the legal and regulatory aspects that support implementation of training activities as a practical learning for cadets. The research’s method is qualitative descriptive. The results showed that the level of effectiveness of the management of the training vessel was effective in the purpose of familiarizing the cadets before carrying out marine practices on commercial vessels. However, there needs to be consistency in the duration of the training implementation. Guidelines for the implementation of training on training ships have not been implemented optimally. There needs to be assignments for lecturers/instructors on board. Programs and training on training ships have not been fully accommodated in the education and training curriculum.